The Necessity of Incorporating an Interposition Flap During Vesicovaginal Fistula Repair: Can Modifying the Method of Vaginal Repair Serve as a Substitute? A Randomized Clinical Trial - Khorami , Mohammad Hatef; Zargham , Mahtab; Taheri , Pegah; Gholipoor , Farshad; Safari, Maede (Urology Journal, 2024)
Purpose: Traditionally, an omental flap is employed to reduce the risk of recurrence of vesicovaginal fistula (VVF) repair. In this study, we employed a modified surgical technique wherein the vaginal defect was closed using Connell sutures, without incorporation of an omental flap, aiming to mitigate potential complications. Material and method: Between 2010 to 2018, the current randomized clinical trial was conducted on 52 women who were candidates for open fistula repair. The patients were randomly allocated into two groups. In one group, the conventional method of fistula repair was performed involving an omental flap, while in the other group, we used a modified approach with a variation in the vaginal wall closure technique. In-hospital variables, including the length of surgery, hospital stay, and occurrences of ileus, were recorded. Patient follow-up extended for one year, with assessments conducted one, six, and twelve months postoperatively. These evaluations encompassed pad test to ascertain success rates and identify any potential complications. Results: The final analysis comprised 49 patients, with an average age of 46.5 years. Baseline characteristics were comparable between the two groups (P-values > 0.05). The modified technique was associated with significantly reduced surgical duration (P = ˂ 0.001), and shorter hospital stays (P < 0.001). Ileus occurrence was reduced, but it was not significant(P = 0.856). However, the success rate showed no significant difference between the groups, with a success rate of 100% for the modified technique compared to 91.6% for the classic O’Conner method (P = 0.288). Conclusion: Based on the findings of this study, vaginal wall closure using Connell sutures during VVF repair demonstrates a success rate equivalent to the classic approach involving an omental flap. Moreover, this technique presents a reduced incidence of adverse effects, along with decreased surgical duration, hospital stay, and postoperative ileus.